Mini-invasive Indirect Distraction in the Treatment of Neglected DRUJ Dislocations—A Novel Surgical Technique - Czinner, Martin; Verstreken, Frederik; Kebrle, Radek (Journal of Wrist Surgery, 2023)
Introduction: This study presents mini-invasive indirect distraction in the treatment of neglected distal radioulnar joint (DRUJ) dislocations as a novel surgical technique. Pure DRUJ dislocation is a rare injury caused by over rotation of the forearm. It is often undiagnosed in an acute setting. There is no consensus on the treatment of neglected dislocations.Materials and methods: We present a group of six patients with neglected pure DRUJ dislocation, treated by a single surgeon between 2012 and 2019.Results: Closed reduction was impossible in six of six patients. The indirect distraction allowed the reduction of the DRUJ in all cases with final stable DRUJ. Forearm rotation returned to normal in four patients, one patient had 50%, and another patient had 60% of the range of forearm. Mean pain dropped from 7 to 0.8 on visual analog scale. At the 2-year follow-up, the mean Disabilities of the Arm, Shoulder, and Hand score was 8 (0–37.5), and minor degenerative X-ray changes were observed in four patients.Level of evidence IV
Keywords: DRUJ; neglected; dislocation; mini-invasive; distraction